Atrial fibrillation in young stroke patients: do we underestimate its prevalence?. Issue 10 (17th May 2013) - Prefasi, D.; Martínez‐Sánchez, P.; Rodríguez‐Sanz, A.; Fuentes, B.; Filgueiras‐Rama, D.; Ruiz‐Ares, G.; Sanz‐Cuesta, B. E.; Díez‐Tejedor, E.
Abstract : Background and purpose: The prevalence of atrial fibrillation (AF) in young stroke patients has rarely been reported and is considered an uncommon ischaemic stroke (IS) aetiology. Our objective was to analyse the prevalence of AF in IS patients up to 50 years of age and its relationship with stroke severity and outcomes. Methods: This was an observational study of consecutive IS patients up to 50 years of age admitted to a stroke centre during a 5‐year period (2007–2011). A complete cardiology study was performed with a daily electrocardiogram and cardiac monitoring for 72 h as well as echocardiography. In cases of stroke of unknown aetiology a 24‐h Holter monitoring was performed. Baseline data, previously or newly diagnosed AF, structural heart disease (SHD) (valvulopathy/cardiomyopathy), stroke severity on admission as measured by the National Institutes of Health Stroke Scale (NIHSS) (moderate‐severe stroke if NIHSS ≥ 8) and 3‐month outcomes according to the modified Rankin Scale (mRS) (good outcome if mRS ≤ 2) were analysed. AF was classified as AF associated with SHD (AF‐SHD) and AF not associated with SHD (AF‐NSHD). Results: One hundred and fifty‐seven patients were included (mean age 43 years, 58.6% male). Fourteen subjects (8.9%) presented with AF, four with AF‐NSHD and 10 with AF‐SHD. AF was previously known in 10 patients (6.3%), two with AF‐NSHD and eight with AF‐SHD. A multivariate analysis showed an independent association between AF and moderate‐severe IS (odds ratio 3.771, 95% CI 1.182–12.028), but AF was not an independent prognostic factor. Conclusion: AF may be more common than expected in young patients with IS and is associated with increased NIHSS scores.